Core bacteria and fungi in response to residue retention and their contribution to soil multifunctionality in maize agroecosystem - Guo, Quankuan; Yu, Yang; Zhang, Shuhan; Guan, Yupeng; Jiang, Nana; Pang, Shuang; Fadda, Carlo; De-Santis, Paola; Bergamini, Nadia; Liu, Xuesheng; Zhang, Ximei; Yang, Wei (Elsevier, 2024)
Core microbiome has been proven to play crucial roles in soil function. However, we still lack knowledge on how core microbiome responds to crop residue retention, and whether they contribute to this process. Consequently, we examined the effect of residue retention on soil core and non-core microbial communities in maize seedling, mature stage and freezing period based on a multi-site field experiment in Sanjiang Plain, Northeast China. Totally, 247 bacterial amplicon sequence variants (ASVs) and 109 fungal ASVs were identified as core microbiota. Both core and non-core bacterial/fungal community composition were significantly influenced by residue retention across all study sites. Especially, the core fungal community shifted towards a saprotroph-dominated community. Normalized stochastic ratio pattern revealed that that deterministic process dominated both core and non-core microbial community assembly processes. Residue retention enhanced the deterministic process of core microbial community assembly, while exhibited opposite effect on non-core microbial community. This study also revealed that soil fungi were more sensitive to residue retention than bacteria, with a larger proportion of core fungi were enriched or depleted by residue retention. In addition, residue retention complicated core bacterial co-occurrence network, while simplified fungal network. Our results pointed out both no reduction in microbial diversity or collapse in microbial network structure after repeated freezing-thawing cycles. The potential function of core microbiome was evaluated through random forest analysis and structural equation model, the results indicated core microbiome contributed more to multifunctionality than non-core microbiome. Overall, this study strengthened our understanding of soil core microbiome in response to residue retention, and highlighted their importance in maintaining soil multifunctionality.